LiBolt Trading / Mohamad Iqram Ab Nasir - Ab Nasir, Mohamad Iqram (2020)
LiBolt Trading is a business that sells electrical appliances and is located in Kota Bharu, Kelantan. It was established on June 28, 2018. This business is one of the electrical appliance businesses in Kelantan that sells many technology-enhanced products and their signature product is a portable power supply named PortaPS. PortaPS is a product designed by the business owner himself and currently being manufactured by a chosen manufacturer of the business. LiBolt Trading is a sole proprietorship business owned by Mr. Mohamad Iqram as the General Manager. For its top management, there are Mr. MohdPawiro as Sales and Marketing Manager, Mr. Iqbal Ali as Financial Manager and Mr. Mohammad Muaz as Administrative Manager